Effect of dietary Cordyceps polysaccharide supplementation on intestinal microflora and immune response of Apostichopus japonicus. (27th June 2021) - Sun, Yongxin; Rabbi, Md Hasim; Ma, Shuhui; Wen, Zhixin; Li, Xuejun; Mi, Rui; Meng, Nang; Li, Yajie; Wang, Qingzhi; Du, Xingfan; Ren, Tongjun
Abstract: A 30‐day feeding trial was conducted to evaluate the effect of Cordyceps polysaccharide (CP) supplement on the breeding of the sea cucumber, Apostichopus japonicus . The dietary treatment groups were as follows: basal diets (N‐con); basal diets along with antibiotic solution soaked weekly (P‐con); and basal diets supplemented with 0.2% CP (T0.2), 0.4% CP (T0.2) and 0.8% CP (T0.8). The results showed that sea cucumber receiving 0.4% CP had the highest diversity index for the intestinal microbiota composition and a significantly higher relative abundance of Bacillus spp., Lactobacillus spp. and Bifidobacterium spp. ( p  < 0.05) than the other groups. Functional prediction showed a significant increase in carbohydrate metabolism and membrane transport after feeding with CP. Significantly improved superoxide dismutase, lysozyme and acid phosphatase activities were observed in the treatment groups when sea cucumbers fed with CP compared with the N‐con and P‐con group ( p  < 0.05). The pathogenicity challenge test showed that a basal diet containing 0.4% or 0.8% CP reduced mortality significantly after injection with infectious Vibrio splendidus . The results suggest that CPs have potential as an alternative to antibiotics to optimize the intestinal microbiota and increase immune responses of A .  japonicus .